Tyro3 Contributes to Retinal Ganglion Cell Function, Survival and Dendritic Density in the Mouse Retina - Blades, Farrah; Wong, Vickie H. Y.; Nguyen, Christine T. O.; Bui, Bang V.; Kilpatrick, Trevor J.; Binder, Michele D. (Frontiers in Neuroscience, 2020)
Retinal ganglion cells (RGCs) are the only output neurons of the vertebrate retina, integrating signals from other retinal neurons and transmitting information to the visual centers of the brain. The death of RGCs is a common outcome in many optic neuropathies, such as glaucoma, demyelinating optic neuritis and ischemic optic neuropathy, resulting in visual defects and blindness. There are currently no therapies in clinical use which can prevent RGC death in optic neuropathies; therefore, the identification of new targets for supporting RGC survival is crucial in the development of novel treatments for eye diseases. In this study we identify that the receptor tyrosine kinase, Tyro3, is critical for normal neuronal function in the adult mouse retina. The loss of Tyro3 results in a direct reduction in photoreceptor and RGC function as measured using electroretinography. The reduction in RGC function was associated with a thinner retinal nerve fiber layer and fewer RGCs. In the central retina, independent of the loss of RGCs, Tyro3 deficiency resulted in a dramatic reduction in the number of RGC dendrites in the inner plexiform layer. Our results show that Tyro3 has a novel, previously unidentified role in retinal function, RGC survival and RGC morphology. The Tyro3 pathway could therefore provide an alternative, targetable pathway for RGC protective therapeutics.